Exposure to contaminants and nutritional intakes in a French vegetarian population. (November 2017) - Fleury, S.; Rivière, G.; Allès, B.; Kesse-Guyot, E.; Méjean, C.; Hercberg, S.; Touvier, M.; Bemrah, N.
Abstract: The NutriNet Santé study collected, on a voluntary basis, the dietary consumption of French vegetarian populations (N = 1766, including 188 vegan individuals) from 18 to 81 years (18–77 years for the vegan). Taking advantage of the availability of contamination data generated in the context of the second French total diet study, dietary exposures of French vegetarian populations to several contaminants were estimated. Results showed that exposures to persistent organic pollutants (PCBs, PCDD/Fs for instance) was dramatically lower than those of the general French population due to the non consumption of food of animal origins. On the other hand, exposures to phytoestrogens, some mycotoxins (T2 and HT2 toxins) and some trace elements (Cd, Al, Sn, Ni) were higher in the vegetarian population compared to those of the general population. Despite some limitations of this approach (both the consumption study and the total diet study were not aimed to estimate dietary exposure of the vegetarian populations), this study showed that dietary habits can dramatically influence the exposure of some contaminants. Highlights: Dietary exposure of French vegetarian populations to several contaminants were estimated. Exposure to persistent organic pollutants was lower than the general population (non consumption of food of animal origins). Exposures to phytoestrogens, some mycotoxins (T2, HT2) and some trace elements (Cd, Al, Sn, Ni) were higher compared to the general population.